Determinan Kinerja Keuangan Pada Perusahaan Holding Perkebunan Nusantara - Himawan, Dhimas Rayendra; Abdani, Fadlil (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p16, 2022)
This study aims to examine the effect of DER, CR, and company growth on financial performance projected by ROA. The research utilizes data from the annual reports of plantation issuers, namely the subsidiary of Holding Perkebunan Nusantara from 2016-2019. The sample determination method uses purposive sampling with an observation period from 2016 to 2019. The use of multiple linear regression analysis is used to test the hypothesis in this study. The results showed that DER, CR, and company growth had a negative and insignificant effect on the financial performance (ROA) of Holding Perkebunan Nusantara. The conclusion of the study is that DER, CR, and growth growth do not play an important role on financial performance (ROA). Keywords: Debt to Equity Ratio; Current Ratio; Company Growth .